Lower Body Weight in Rats Under Hypobaric Hypoxia Exposure Would Lead to Reduced Right Ventricular Hypertrophy and Increased AMPK Activation - Flores, Karen; Siques, Patricia; Brito, Julio; Ordenes, Stefany; Arriaza, Karem; Pena, E.; León-Velarde, Fabiola; López, Rosario; López de Pablo, Ángel L.; Arribas, Silvia (Frontiers in Physiology, 2020)
Background: Both chronic hypoxia (CH) and long-term chronic intermittent hypoxia (CIH) exposure lead to right ventricular hypertrophy (RVH). Weight loss is an effective intervention to improve cardiac function and energy metabolism in cardiac hypertrophy. Likewise, caloric restriction (CR) also plays an important role in this cardioprotection through AMPK activation. We aimed to determine the influence of body weight (BW) on RVH, AMPK and related variables by comparing rats exposed to both hypoxic conditions. Methods: Sixty male adult rats were separated into two groups (n=30 per group) according to their previous diet: a caloric restriction (CR) group and an ad libitum (AL) group. Rats in both groups were randomly assigned to 3 groups: a normoxic group (NX, n=10), a CIH group (2 days hypoxia/2 days normoxia; n= 10) and a CH group (n=10). The CR group was previously fed 10 g daily, and the other was fed ad libitum. Rats were exposed to simulated hypobaric hypoxia in a hypobaric chamber set to 428 Torr (the equivalent pressure to that at an altitude of 4,600 m above sea level) for 30 days. Measurements included body weight; hematocrit; serum insulin; glycemia; the degree of RVH (Fulton´s index and histology); and AMPK, mTOR, and PP2C expression levels in the right ventricle determined by western blotting. Results: A lower degree of RVH, higher AMPK activation, and no activation of mTOR were found in the CR groups exposed to hypobaric hypoxia compared to the AL groups (p<0.05). Additionally, decreased glycemia and serum insulin levels were observed. Interestingly, PP2C expression showed an increase in the AL groups but not in the CR groups (p<0.05). Conclusion: Maintaining a low weight before and during exposure to high-altitude hypoxia, during either CH or CIH, could prevent a major degree of RVH. This cardioprotection would likely be due to the activation of AMPK. Thus, body weight is a factor that might contribute to RVH at high altitudes.